Evaluation of cognitive functions in diabetic patients - Cakir, Emre; Harmankaya, Nazmiye Ozlem; Cengiz, Hasret; Varim, Ceyhun (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes Mellitus is an independent risk factor for cognitive impairment and dementia. In this study, authors investigated cognitive functions in the diabetes and control group with Mini Mental State Examination (MMSE). Authors analyzed the association of cognitive status with age, sex, duration of diabetes, insulin use and HbA1c in diabetic patients. Methods: Fifty patients with diabetes diagnosed between the ages of 50 and 70 who applied to this Diabetes and General Internal Medicine Clinics between January 2017 and September 2017 were included. Fifty patients with nondiabetes diagnosed with similar age and demographic characteristics were included in the control group. MMSE was applied to both groups. In the diabetic group, cognitive functions were investigated in relation with age, gender, duration of diabetes, insulin usage and HbA1c. Results: The MMSE score in diabetic patients was lower than the control group (p<0.05). In addition, cognitive impairment in diabetic patients was associated with duration of diabetes and HbA1c level. There wasn’t significant difference was found between cognitive impairment and age, sex, insulin use. Conclusions: Diabetes Mellitus is a risk factor for cognitive impairment and dementia with many possible mechanisms. In the routine, there is no screening for cognitive impairment and dementia in diabetic patients; but if authors detect early cognitive impairment, authors can prevent cognitive impairment progression to dementia with medical treatment and cognitive exercises.